SELF EFFICACY MAHASISWA TERHADAP PEMBELAJARAN FISIKA DASAR SELAMA PANDEMI COVID 19 DI UIN IMAM BONJOL PADANG (Students' Self-Efficacy Towards Learning of Basic Physics During The Covid-19 at Imam Bonjol State Islamic University of Padang) - Hurriyah Hurriyah; lufri lufri; andromeda andromeda; fatni mufit (Jurnal Ilmiah Didaktika, 2022)
The purpose of this study was to determine student self-efficacy in learning Basic Physics at the Tadris IPA Physics study program at UIN Imam Bonjol Padang during the covid 19 outbreak. This type of descriptive research was conducted in this study, with 45 first semester students as the population. This study uses a questionnaire as a data collection tool that has been validated by experts. Based on the results of the study, it was found that the self-efficacy of students in basic physics subjects during online learning was in the good/high category (71.11%). From the aspect of the dimension of self-efficacy, it was also obtained that the average of each dimension obtained high results or in the good category. This means that students have awareness and belief in their potential and can adapt to learning in pandemic conditions. The obstacle for students in learning basic physics is that the implementation of practicum is not optimal. the solution is the need for regulation from educational institutions, especially in practicum courses to continue to practice in the laboratory by paying attention to health protocols.